Certification process of aircraft airworthiness dynamics simulation - Кордянин, Ю. И. (Proceedings of National Aviation University (archive), 1999)
The structure and analytical description of certification process model of airworthiness, algorithm of statistical identification of mathematical model and examples of model application for problems of airworthiness regulation in conditions of Ukraine are resulted